LOCAL CONSERVATION INNOVATION: SEARCHING LOCAL HISTORY, CULTURE AND TRADITIONS - Praneet , Yuttana (Journal of MCU Nakhondhat, 2021)
This article was as; 1) study the existential culture and the preservation of local traditions. 2) Tourism community program. History, culture, local traditions and 3) Propose a policy and strategy for the conservation of cultural traditions. It is a research in development and applied. By focusing on the participation process of stakeholders, interviewing 30 key informants, by Community development provincial, Cultural office provincial. Tourism and Sports office, Local government organization, Local leader and the public sector. and a group of 10 people, consisting of government agencies. Local government organization Local leader and private networks. sources were analyzed by descriptive content. The research results were found that 1) Identity, culture and conservation of local traditions Politics and governance have the ideals of belief in their leaders. Respect parents, with solidarity and unity of the people in the community, adhering to the principle of leaders to sustain the country being a moral community, leading politics, n terms of culture, there is a way of life based on raw materials that are good in the community. For the center of the community’s way of life, the mind has values ​​by being ordained according to tradition. Tradition is creating gratitude through "Rice Culture" Forest ordination tradition Determine the destiny of the river. 2) Tourism Community Program History, culture and local traditions with 3 routes: "Light Green Route", a network of self-sufficiency communities, occupation groups. "Brown Route" Thai way of life travel plan Forest ordination and worship activities for 9 temples, "White Route" travel plans Nawatwithi of Good stuff, Nong Bua District. 3) Policies and strategies for conservation of cultural traditions by using a network of self-sufficiency communities Thai way of life and Nawatwithi of Good stuff, Nong Bua District, Driving community tourism activities promote and develop local tourism agricultural strategy reduce production costs, by bringing local wisdom and natural resources at the local to be adapted for soil conservation solve poverty, reduce disparity developing potential and quality of life of people in the community.